PERANCANGAN BUKU POP UP CERITA AER MATA EBUH SEBAGAI UPAYA MEDIA MENGENALKAN LEGENDA ASLI AROSBAYA BANGKALAN MADURA KEPADA ANAK - ANAK - Munthasor, Ghavin Nizar; Yurisma, Dhika Yuan; Fahminnansih, Fenty (Jurnal Art Nouveau, 2018)
The story of Aer Mata Ebuh is from Arosbaya sub-district Bangkalan Madura. The story of Aer Mata Ebuh is a story about the obedience of a wife to the husband and the sacrifice of a mother to her children, but unfortunately there is still very little media that contains the story as a medium of learning. From that case researchers want to design the learning media that contains the story. This research uses qualitative method, that is by observation, interview, documentation and literature study to get data to design the media. The media is a pop up book that is useful as a medium of learning and media to introduce the story to children - children.